Accumulation of DNA damage and alteration of the DNA damage response in monoclonal B-cell lymphocytosis and chronic lymphocytic leukemia - Popp, Henning; Flach, Johanna; Brendel, Susanne; Ruppenthal, Sabrina; Kleiner, Helga; Seifarth, Wolfgang; Schneider, Sven; Schulze, Torsten; Weiß, Christel; Wenz, Frederik; Hofmann, Wolf-Karsten; Fabarius, Alice (Leukemia and lymphoma, 2019)
Accumulation of DNA damage and alteration of the DNA damage response (DDR) are critical features of genetic instability that is presumed to be implicated in the pathogenesis of monoclonal B-cell lymphocytosis (MBL) and chronic lymphocytic leukemia (CLL). Here, we show increased numbers of γH2AX foci, a marker of DNA double-strand breaks (DSB), in CD19+ cells of CLL patients as compared to CD19+ cells of MBL patients and healthy individuals. Furthermore, numerous γH2AX/53BP1 foci in CLL cells suggest activation of error-prone non-homologous end-joining repair mechanisms. Signatures of DDR proteins further indicate alterations of the DDR in CLL in contrast to a largely regular activation in MBL and healthy controls. In summary, our results provide evidence for the stepwise accumulation of DNA damage in the progression of MBL towards CLL and suggest increased DNA damage, error-prone DNA repair and altered DDR signaling to be critical mechanisms of clonal evolution in MBL and CLL.